Prevalence of and Factors Associated with MRSA among Patients with Hand Infection Treated in a Public Tertiary Hospital - ARELLANO, TRISTAN JAY; Gandionco, Jessica Anne; Valenzuela, Madonna (Philippine Journal of Orthopaedics, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) poses significant challenges in managing hand infections, especially in resource-limited settings like the Philippines. Despite its global prevalence, data on MRSA-specific hand infections in Filipino patients remain scarce. This study aimed to determine the prevalence of MRSA and identify associated factors among patients treated for hand infections at a public tertiary hospital. Methodology: A retrospective, cross-sectional study was conducted at Jose B. Lingad Memorial General Hospital from February 2022 to January 2024. Data from 233 patients treated for hand infections were analyzed. Variables examined included demographics, employment status, infection etiology, comorbidities, traditional medicine use, infection location, and classification. Statistical analyses were performed to identify associations with MRSA. Result: MRSA prevalence was 30%, with bite wounds and use of traditional medicine showing significant associations (p = 0.002). Educational attainment was also linked to MRSA status, with unschooled individuals having a higher prevalence (p = 0.027). Other variables, such as age, gender, employment, comorbidities, and infection classification, showed no significant associations. Conclusion: This study highlights the high prevalence of MRSA in hand infections, with traditional medicine use and bite wounds as key risk factors. The findings underscore the need for targeted educational campaigns, early intervention protocols for bite wounds, and community engagement to address traditional medicine practices. These measures could improve MRSA management and prevention in similar settings. Keywords: Methicillin-resistant Staphylococcus aureus, hand infections, risk factors, traditional medicine, Philippines